Influence of science education on mental health of adolescents based on virtual reality - Wu, Bo; Zheng, Changlong; Huang, Benjamin (Frontiers in Psychology, 2022)
This work is developed to explore the form of mental health education, strengthen scientific educational ideas, and improve the effect of psychological therapy. Virtual Reality (VR) technology is innovatively applied in adolescent mental health treatment and education. Based on this, the mental health treatment and system design based on virtual reality technology are discussed, and the feasibility of applying VR technology to adolescent mental health education is explored. Secondly, the research concept of adolescent mental health is discussed. Based on the VR platform set up, questionnaire survey is implemented to analyze the factors influencing the mental health of primary and secondary school students in Xi ‘an, Shaanxi Province (the permission of the adolescent guardian is obtained during the interview), and five factors are obtained. On this basis, the adolescent mental health treatment system based on VR is designed, and the effectiveness of the system is tested and evaluated. The results show that the integrated delay of the VR equipment used is 29 ms, which can effectively provide service. There are significant differences in mental health status among adolescents of different genders, different ages, only children and non-only children, parents’ accompaniment during growing up, and urban and rural adolescents. Finally, after three months of psychological treatment, the mental health score of the experimental group of teenagers is 50 to 55 points. However, the mental health scores of the control group remain at 56~65 points, indicating that the mental health treatment system designed in this work can effectively help the adolescents to improve their mental health, thus proving the effectiveness of the system. To sum up, this work provides scientific reference for adolescent mental health education in schools. Psychological treatment system can help teenagers improve their psychological problems and promote the development of mental health education.